48.2k views
0 votes
Solve for x. 3^x−1=9^x+2
Enter your answer in the box.

1 Answer

4 votes

Answer:

-5 =x

Explanation:

3^(x-1) = 9^(x+2)

Replace 9 with 3^2

3^(x-1) = 3^2^(x+2)

We know that a power to a power means the powers are multiplied

a^b^c = a^(b*c)

3^(x-1) = 3^(2x+2)

When the bases are the same, the powers have to be the same

x-1 = 2x+4

Subtract x from each side

x-x-1 =2x-x+4

-1 =x+4

Subtract 4 from each side

-1-4 =x+4-4

-1-4 = x

-5 =x

User Karl Entwistle
by
5.3k points